Implementasi Program Kegiatan Keagamaan dalam Meningkatkan Karakter Religius Siswa di MTsN 5 Jombang - Rahmatulloh R; Ammar Zainuddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Religious character is the first and main character that must be instilled in children as early as possible, which becomes the basis of religion in the lives of individuals, society and the Indonesian nation. Religious character is not only related to religious relationships but also to relationships between human beings. Familiarization with religious programs in schools has a very important role in cultivating the character formation of children as they grow older, because schools are formal institutions that are the initial foundation for students at the next level. This research was conducted to find out how the implementation of religious activity programs, especially at MTsN 5 Jombang, develops students' religious character. This type and approach to research uses qualitative research with a case study type. Data collection methods were carried out using interviews, observation and documentation. Data analysis was carried out through the stages of data reduction, data display, data verification and drawing conclusions. The data validity test was carried out using the triangulation method. The results of this research illustrate that: 1) The forms of religious activity programs at MTsN 5 Jombang include: tadarus Al-Qur'an and reading asmaul khusna, dhuha prayers, memorizing the Al-Qur'an, midday prayers in congregation at the school mosque, infaq which is held every Friday. 2) Implementation of the religious activity program in developing religious character at MTsN 5 Jombang is as follows: First, school policy in which all school members participate in all forms of religious activities implemented by the school. Second, the commitment of the school community is realized through the participation and cooperation of all school residents led by the head of MTsN 5 Jombang. Third, creating a religious atmosphere by setting a schedule for implementing religious activity programs.